The key role of the NUDT3 gene in lung adenocarcinoma progression and its association with the manganese ion metabolism family - Deyong Ge; Xinyu Xu; Liyi Fang; Huihui Tao (Discover Oncology)
Abstract Background Lung adenocarcinoma is one of the most common malignant tumors worldwide. Its complex molecular mechanisms and high tumor heterogeneity pose significant challenges for clinical treatment. The manganese ion metabolism family plays a crucial role in various biological processes, and the abnormal expression of the NUDT3 gene in multiple cancers has drawn considerable attention. This study aims to systematically analyze the expression characteristics of the NUDT3 gene in lung adenocarcinoma and its association with tumor progression, integrating single-cell transcriptomic analysis and experimental validation using cell lines. Methods This study employed a comprehensive set of analytical approaches. Single-cell transcriptomic analysis of two normal and four lung adenocarcinoma samples from the GSE149655 dataset was performed using the Seurat package to identify and annotate distinct cell populations, focusing on epithelial and macrophage subtypes. Non-negative matrix factorization (NMF) and gene set variation analysis (GSVA) were applied to assess the functional enrichment and expression profiles of the manganese ion metabolism family across 14 cancers. Quantitative PCR (qPCR) was conducted to evaluate the relative mRNA expression of NUDT3 in A549 lung adenocarcinoma cell lines compared to BEAS-2B normal bronchial epithelial cell lines. GAPDH was used as the reference gene for normalization, and the relative expression levels of NUDT3 in these cell lines were analyzed to confirm bioinformatics findings. Results NUDT3 was found to be significantly upregulated in lung adenocarcinoma and highly correlated with tumor mutation burden (TMB) and mutation enrichment (MEs). Single-cell transcriptomic analyses demonstrated elevated NUDT3 expression in lung adenocarcinoma epithelial cells, with expression levels increasing in cells associated with advanced tumor stages. Furthermore, qPCR analysis confirmed the upregulation of NUDT3 in A549 cells compared to BEAS-2B cells, consistent with transcriptomic data. These results also highlighted significant expression differences of the manganese ion metabolism family across various cancers, including BLCA, BRCA, and COAD, with notable NUDT3 mutations enriched in these cancers. Conclusion This study underscores the critical role of NUDT3 in lung adenocarcinoma progression and its potential as a therapeutic target. These findings contribute to the understanding of the manganese ion metabolism family in cancer biology and provide a foundation for precision therapies targeting NUDT3 in lung adenocarcinoma.